Simplify (-3a)^2 +(-3a)^-2 * (-3a^-2)

Please explain how you arrive at the answer.Thanks

### 1 Answer | Add Yours

`(mxxn)^p=m^pxxn^p`

`m^(-n)=1/m^n,`

`m^lxxm^p=m^(l+p)`

`(-3a)^2 +(-3a)^-2 * (-3a^-2)`

`=(-3)^2a^2+(-3)^(-2)a^(-2)xx(-3)^(-2)a^(-2)`

`=9a^2+(1/(-3)^2)(1/a^2)xx(1/(-3)^2)(1/a^2)`

`=9a^2+(1/9)(1/a^2)xx(1/9)(1/a^2)`

`=9a^2+(1/(81))(1/a^4)`

`=9a^2+1/(81a^4)`

`` Ans.

### Join to answer this question

Join a community of thousands of dedicated teachers and students.

Join eNotes